Isavuconazole as Primary Antifungal Prophylaxis in Patients With Acute Myeloid Leukemia or Myelodysplastic Syndrome: An Open-label, Prospective, Phase 2 Study. (1st April 2020) - Bose, Prithviraj; McCue, David; Wurster, Sebastian; Wiederhold, Nathan P; Konopleva, Marina; Kadia, Tapan M; Borthakur, Gautam; Ravandi, Farhad; Masarova, Lucia; Takahashi, Koichi; Estrov, Zeev; Yilmaz, Musa; et al.
Abstract: Background: Mold-active primary antifungal prophylaxis (PAP) is routinely recommended in neutropenic patients with newly diagnosed acute myeloid leukemia (AML) or high-risk myelodysplastic syndrome (MDS) undergoing remission-induction chemotherapy (RIC). Isavuconazole (ISAV) is an extended spectrum mold-active triazole and has superior tolerability and fewer significant drug–drug interactions compared with other triazoles. Methods: In our investigator-initiated, phase 2 trial, treatment-naive adult patients with AML or MDS starting RIC received ISAV per the dosing recommendations in the US label until neutrophil recovery (absolute neutrophil count [ANC] ≥ 0.5 × 10 9 /L) and attainment of complete remission, occurrence of invasive fungal infection (IFI), or for a maximum of 12 weeks. The primary endpoint was the incidence of proven/probable IFI during ISAV PAP and up to 30 days after the last dose. Results: Sixty-five of 75 enrolled patients received ISAV PAP (median age, 67 years, median ANC at enrollment, 0.72 × 10 9 /L). Thirty-two patients (49%) received oral targeted leukemia treatments (venetoclax, FTL3 inhibitors). Including the 30-day follow-up period, probable/proven and possible IFIs were encountered in 4 (6%) and 8 patients (12%), respectively. ISAV trough serum concentrations were consistently > 1 µg/mL, showed low intraindividual variation, and were not significantly influenced by chemotherapy regimen. Tolerability of ISAV was excellent, with only 3 cases (5%) of mild to moderate elevations of liver function tests and no QTc prolongations. Conclusions: ISAV is a safe and effective alternative for PAP in patients with newly diagnosed AML/MDS undergoing RIC in the era of recently approved or emerging small-molecule antileukemia therapies. Clinical Trials Registration: NCT03019939. Abstract : In this prospective study, isavuconazole prophylaxis was safe in 65 neutropenic patients with newly diagnosed acute myeloid leukemia/myelodysplastic syndrome undergoing remission-induction chemotherapy, including 32 who received venetoclax and/or FLT3 inhibitors. Four patients (6%) had probable/proven breakthrough fungal infections. Survival rate was 92%.